Chemo‐ and Regioselective Anionic Fries Rearrangement Promoted by Lithium Amides under Aerobic Conditions in Sustainable Reaction Media. Issue 37 (19th May 2022) - Ghinato, Simone; De Nardi, Federica; Bolzoni, Paola; Antenucci, Achille; Blangetti, Marco; Prandi, Cristina
Abstract: A straightforward and efficient protocol to promote the metalation/anionic Fries rearrangements of O ‐aryl carbamates, using for the first time a lithium amide as metalating agent under aerobic/ambient‐friendly reaction conditions, is reported. This approach enables the sustainable preparation of salicylamide derivatives with high levels of chemoselectivity within ultrafast reaction times, working at room temperature in the presence of air/moisture, and using environmentally responsible cyclopentyl methyl ether as a solvent. Furthermore, the regioselective manipulation of O ‐2‐tolyl carbamates has been accomplished using interchangeably alkyllithiums or lithium amides, with an unexpected beneficial contribution from the employment of biorenewable protic eutectic mixtures as non‐innocent reaction media. Abstract : A simple, scalable, and sustainable access to salicylamides from O ‐aryl carbamates was achieved using lithium amides as easy‐to‐handle metalating agents under bench‐type aerobic conditions. Tunable regioselective ortho ‐ and lateral metalations in eco‐friendly cyclopentyl methyl ether (CPME) allow fast anionic migrations under air, with an unexpected beneficial contribution from biorenewable protic eutectic mixtures.